Magnetic Superhydrophobic Polymer Nanosphere Cage as a Framework for Miceller Catalysis in Biphasic Media. Issue 6 (12th May 2014) - Zheng, Zhi; Wang, Jianli; Chen, Hualiang; Feng, Linbin; Jing, Ren; Lu, Meizhen; Hu, Bao; Ji, Jianbing
Abstract This study demonstrated the use of a magnetic superhydrophobic polymer nanosphere cage derived from a Pickering emulsion as a framework for miceller catalysis in biphasic media. We designed this system through the covalent stabilisation of active site (2, 2, 6, 6‐tetramethylpiperidine 1‐oxyl)‐grafted amphiphiles onto the magnetic hydrophobic core to form a micelle‐like architecture and used it as a Pickering emulsifier to develop a new kind of micelle‐catalysed biphasic system. The catalysis results reveal that these fixed micelle‐tethered 2, 2, 6, 6‐tetramethylpiperidine 1‐oxyl catalysts demonstrate much higher activity than their soluble counterparts in the biphasic Montanari oxidation of alcohols, which could be due to the unique properties of Pickering emulsion and miceller catalysis. In addition, the excellent magnetic response ensures the efficient recycling of the catalyst by magnetic decantation. The catalyst can be recycled at least 10 times without significant loss of activity or degradation of magnetic susceptibility. Moreover, this study demonstrates that this new Pickering emulsion‐based and micelle‐catalysed biphasic system is technically simple and practically applicable.